Formulation, characterization and in vitro bioaccessibility evaluation of mixed soy lecithin-based squalene liposome-encapsulated quercetin with added phytosterols - Pakbaten Toopkanloo, Sahar (2020)
Liposomes, resembling biomembranes, are effective delivery systems for lipid bioactive compounds but face instability from various stressors. Understanding the impact of incorporated materials on membrane integrity is crucial. Squalene (SQ) conjugation to phospholipids enhances lipophilicity, while cholesterol (CH), β- sitosterol (βS), and stigmasterol (ST) modify membrane properties. However, quercetin's (QU) insolubility hampers absorption, necessitating novel nanovesicles for solubilization. In the first part of the study, the effect of membrane composition and concentrations on the degradation of mixed soy lecithin (ML)-based liposomes was investigated. Liposomes were prepared using SQ, CH, and Tween 80 (TW80) to increase bilayer deformability. Liposome batches were prepared with and without SQ, and their zeta potential, particle size, and antioxidant activity against UV-induced ROS generation were evaluated. Results showed SQ association reduced size without extra energy input and improved stability and antioxidant activity. Additionally, different lipid compositions significantly influenced physical and chemical characteristics. The second part focused on enhancing the photostability, integrity, and antioxidant capacity of ML-based liposomes by adjusting the formulation within the membrane. QU encapsulation in ML-based liposomes and the concentration-dependent solubility of QU were investigated. A combination of βS and ST was used to modulate ML bilayers, maintaining liposome function. Encapsulation efficiency measurements revealed effective QU encapsulation using specific concentrations of βS and ST. The presence and type of phytosterols affected membrane integration characteristics and photostability. In the subsequent part, the effects of environmental conditions on liposome stability and antioxidant capacity were evaluated. Liposomes stored at 4°C for 8 weeks showed decreased stability over time, but remained stable for the first 6 weeks. Differential scanning calorimetry results showed desirable interaction with liposome membrane models. X-ray diffraction patterns revealed variations in lattice distortion and structural disorder upon changing membrane composition. Finally, the in vitro bio-accessibility of QU-loaded ML-based liposomes was examined. Different membrane stabilizers influenced QU bio-accessibility, correlating with entrapment efficacy. The phase transition temperature in liposomes changed with the addition of stabilizers, indicating enhanced membrane stability. This highlights the potential of well-designed ML-based liposomes to increase the stability and bio-accessibility of lipophilic bioactives like QU. In conclusion, the presence of different lipid compositions significantly influenced the physicochemical characteristics of the liposomes, including entrapment efficacy and photodamage transformation.